Limitations on the Authority of the Constitutional Court as a Positive Legislator - Anugrah, Narendra Putra; Hadi, Syofyan (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The authority of the Constitutional Court in Indonesia’s constitutional system has shifted from merely being a negative legislator to a tendency toward becoming a positive legislator. This phenomenon is reflected in various decisions that not only invalidate norms that contradict the Constitution but also establish new legal norms. This study aims to examine the urgency of limiting the Constitutional Court’s authority in acting as a positive legislator and to formulate a limitation model that prevents the Court from exceeding legislative boundaries. This research uses a normative legal method with statutory, case, and conceptual approaches and is analyzed prescriptively and critically based on primary and secondary legal materials. The findings show that the Constitutional Court’s expansive role as a positive legislator has the potential to lead to judicial supremacy and juristocracy, which are inconsistent with the principle of separation of powers. Therefore, limiting the Constitutional Court’s authority is necessary to maintain the constitutional balance among branches of state power. This study proposes the use of Mahfud MD’s “Ten Limiting Guidelines” as a normative framework, complemented by two original models: the Constitutionally Bounded Interpretation Protocol, which emphasizes that judicial interpretation must remain confined to the text, structure, and principles of the Constitution; and the Institutional Dialogue Model, which encourages legislative involvement in the follow-up to Constitutional Court decisions. These models aim to ensure that the Constitutional Court remains within its constitutional role as guardian of the Constitution, without encroaching upon the legislative domain